Proceedings of the 12th International Conference on Robotics, Vision, Signal Processing and Power Applications - Ahmad, Nur Syazreen; Mohamad-Saleh, Junita; Teh, Jiashen (Lecture Notes in Electrical Engineering, 2024)
XIV, 595 p. 254 illus., 211 illus. in color.